1997
DOI: 10.1111/j.1524-4725.1997.tb00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine Porocarcinoma

Abstract: Eccrine porocarcinoma is a malignant tumor of eccrine sweat glands. It is a very rare, slow growing tumor and clinically resembles other skin cancers. We report a case and review its clinical and pathological features. These tumors have a propensity for local recurrence, and wide excision with negative margins is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…EP may result from malignant transformation of a benign eccrine poroma or occur de novo. [3][4][5] The largest series of cases studied to date demonstrated that EP most commonly involves lower extremities, trunk, and head. 6 There is a predilection for elderly patients in the fifth to eighth decades of life.…”
mentioning
confidence: 99%
“…EP may result from malignant transformation of a benign eccrine poroma or occur de novo. [3][4][5] The largest series of cases studied to date demonstrated that EP most commonly involves lower extremities, trunk, and head. 6 There is a predilection for elderly patients in the fifth to eighth decades of life.…”
mentioning
confidence: 99%
“…The lesions are most commonly found on the lower extremities, followed by the head, scalp, upper extremities, trunk and abdomen (1,(5)(6)(7)(8)(9)(10)(11)(12)(13). This malignancy most commonly affects elderly patients with an average age of 67 at the time of diagnosis, but may occur at any age (1-13).…”
Section: Discussionmentioning
confidence: 97%
“…Eccrine porocarcinoma may appear as a nodule, verrucous cauliflower-like infiltrative plaque or as a polypoid lesion that is frequently ulcerated and may bleed (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Multinodularity, rapid growth and ulceration may be associated with either local recurrence or metastasis (1,13).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The ducts are located in the dermis and epidermis. The straight intradermal portion of the duct is the syrinx, and the coiled intradermal portion opening onto the skin surface is the acrosyringium (9,10). Tumours of the syrinx are termed syringomas and tumours of the acrosyringium are poromas.…”
Section: Anatomy Of the Sweat Duct Apparatusmentioning
confidence: 99%